Pearls in the appendix (Myxoglobulosis) : a case report - Vidyachandra Gandhi (Shiraz University of Medical Sciences, 2020)
We report a rare variant of mucocele of the appendix. An elderly gentleman was admitted with symptoms and signs of acute appendicitis. He underwent laparoscopic converted open appendicectomy. On exploration there were pearls or fish egg like globular material along with jelly in and around the appendix. On examination of the specimen a differential diagnosis of hydatid cyst or pseudomyxoma was considered. On microscopic examination, the globules consisted of eosinophilic laminations of mucin surrounding an amorphous granular core. After histopathological examination, our case was diagnosed as myxoglobulosis of the appendix.Acute appendicitis is a common clinical problem and appendisectomy a regular surgery. The clinician should be aware of this entity of myxoglobulosis, to avoid confusion with pseudomyxoma or hydatid cyst. Presence of typical fish eggs or pearls like globular structures in and around the appendix is suggestive of myxoglobulosis. Appendisectomy is curative treatment for patients with myxoglobulosis of appendix and there are no reports of its recurrence.